2020
DOI: 10.1002/adsc.202000838
|View full text |Cite
|
Sign up to set email alerts
|

Benzyl Palladium Intermediates: Unique and Versatile Reactive Intermediates for Aromatic Functionalization

Abstract: Aromatic functionalizations are of current interest and importance in organic chemistry, recent transition‐metal catalyzed reactions can transform inert C−H bond into C−X (X=C, O, N, etc.) bonds, greatly enriching aromatic chemistry and related fields. Some well‐known palladium‐containing intermediates such as palladacycles and allylpalladium intermediates play an important role in organic conversions. Similar with allyl group, benzyl group also possesses the capability of stabilizing palladium through η3‐bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 90 publications
0
19
0
Order By: Relevance
“…Very recently, we published a review article on the aromatic functionalization via reactive benzylpalladium intermediates. [9] Herein, we will mainly summarize our studies on palladiumcatalyzed three-component coupling reactions via benzylpalladium intermediates, as well as the related studies reported by other groups.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, we published a review article on the aromatic functionalization via reactive benzylpalladium intermediates. [9] Herein, we will mainly summarize our studies on palladiumcatalyzed three-component coupling reactions via benzylpalladium intermediates, as well as the related studies reported by other groups.…”
Section: Introductionmentioning
confidence: 99%
“…benzyl chlorides), and not nucleophiles, as is the case in our system. 24 While a number of mechanistic manifolds can be envisioned leading to such side-products, one possibility is illustrated in the beige inset in Scheme 10C . Assuming a canonical oxidative addition/transmetallation path, species 33inv could arise from the isomerization of the Pd( ii )-benzyl fragment to one of its para -palladated forms prior to reductive elimination.…”
Section: Resultsmentioning
confidence: 99%
“…This methodology is advantageous because of the high availability of haloarenes as a starting material and the convergency of the reaction. The key finding in these reactions was the generation of a benzyl–Pd intermediate , by the action of haloarenes and diazo compounds such as TMS diazomethane and N -tosylhydrazones . We envisaged that this type of reaction can be applied to the synthesis of 1-azaspirocycles using bromoarenes bearing an aminoalkyl chain through an intramolecular C–N bond formation on a benzyl–Pd species.…”
mentioning
confidence: 99%